2021
DOI: 10.1111/jfpp.15841
|View full text |Cite
|
Sign up to set email alerts
|

Application of microencapsulated probiotic Bifidobacterium animalis ssp. lactis BB‐12 in Italian salami

Abstract: The search for health and wellness is one of the main trends in the food industry. Manufacturers have focused on developing food products with natural and innovative ingredients, such as probiotics, which aimed to obtain foods with greater health benefits (Wójciak et al., 2016).Probiotics are live microorganisms that when administered in adequate amounts confer health benefits on the host (Hill et al., 2014).Bifidobacterium animalis ssp. lactis (BB-12) are lactic acid-producing, gram-positive, rod-shaped, nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The more water present in the product, the greater luminosity it has, because the loss of water can cause its darkening. Because of that, the values found for L. casei show less luminosity and yellowish color when compared to the other two assays [26]. The "b*" values refer to the consumption of oxygen by lactic acid bacteria during the exponential phase, which in a study of salami added to rice had results between 5.45 and 14.96, meaning improved visual characteristics for the fermented processed food [9,23].…”
Section: Physical and Physicochemical Analysesmentioning
confidence: 92%
See 2 more Smart Citations
“…The more water present in the product, the greater luminosity it has, because the loss of water can cause its darkening. Because of that, the values found for L. casei show less luminosity and yellowish color when compared to the other two assays [26]. The "b*" values refer to the consumption of oxygen by lactic acid bacteria during the exponential phase, which in a study of salami added to rice had results between 5.45 and 14.96, meaning improved visual characteristics for the fermented processed food [9,23].…”
Section: Physical and Physicochemical Analysesmentioning
confidence: 92%
“…At the end of maturation, the acidification kept hitting pH levels between 5.0 and 5.3, which coincides with the isoelectric point of meat proteins, causing a faster water release in the product, bringing on a reduction in the capacity of the meat to retain water and facilitating the drying process of the final product [22,26].…”
Section: Processing Of the Salami-type Fermented Sausagesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more studies need to be conducted to confirm or rule out these claims. Oliveira Gomes et al [9] studied the application of microencapsulated Bifidobacterium animalis ssp. lactis BB-12 in Italian salami assuming that these encapsulated bacteria may not have contributed to the lowering and raising of the pH.…”
Section: Changes In Phmentioning
confidence: 99%
“…Muthukumarasamy and Holley [8] studied the microbiological and sensory qualities of dry fermented sausages containing Lactobacillus reuteri microencapsulated in alginate, with the authors concluding that the encapsulation process allowed the probiotics to survive in sufficient quantities to be considered functional. Years later, Oliveira Gomes et al [9] found that Bifidobacterium animalis ssp. lactis (BB-12) encapsulated by spray drying did not affect the quality and sensory characteristics of Italian salami, remaining viable during 45 days of storage.…”
Section: Introductionmentioning
confidence: 99%